2019
DOI: 10.1111/tpj.14378
|View full text |Cite
|
Sign up to set email alerts
|

The ethylene response factor VaERF092 from Amur grape regulates the transcription factor VaWRKY33, improving cold tolerance

Abstract: Summary Cold stress is a major limiting factor in grape (Vitis) productivity. In this study, we characterized a cold‐responsive ethylene response factor (ERF) transcription factor, VaERF092, from Amur grape (Vitis amurensis). VaERF092 expression was induced by both low temperatures and the ethylene precursor 1‐aminocyclopropane‐1‐carboxylate (ACC), but was suppressed by treatment with the ethylene inhibitor aminoethoxyvinylglycine (AVG) under cold conditions. Ectopic expression of VaERF092 in Arabidopsis thali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 87 publications
0
59
0
Order By: Relevance
“…Zhang et al [49] suggested that overexpression of VaWRKY12, whose nuclear translocation increased under low temperature, enhanced the cold tolerance of Arabidopsis and grapevine calli and significantly increased the expression of antioxidant-related genes. Under cold stress, VaWRKY33 can be regulated by ethylene response factor VaERF092 through binding to its promoter GCC-box, leading to enhanced cold stress tolerance [50]. In our study, arahy.E3SE4T and arahy.EVAW89, orthologous to A. thaliana WRKY70 and WRKY53, were significantly upregulated in NH5 under cold stress.…”
Section: Discussionmentioning
confidence: 63%
“…Zhang et al [49] suggested that overexpression of VaWRKY12, whose nuclear translocation increased under low temperature, enhanced the cold tolerance of Arabidopsis and grapevine calli and significantly increased the expression of antioxidant-related genes. Under cold stress, VaWRKY33 can be regulated by ethylene response factor VaERF092 through binding to its promoter GCC-box, leading to enhanced cold stress tolerance [50]. In our study, arahy.E3SE4T and arahy.EVAW89, orthologous to A. thaliana WRKY70 and WRKY53, were significantly upregulated in NH5 under cold stress.…”
Section: Discussionmentioning
confidence: 63%
“…A new approach to identifying candidates for the remaining steps takes advantage of publicly available 'omics' data banks and analysis tools. Gene co-expression networks (GCNs) are an emerging resource to study grapevine metabolism (Malacarne et al, 2016;Vannozzi et al, 2018), fruit development/ripening (Massonnet et al, 2017) and stress responses (Savoi et al, 2017;Sun et al, 2018Sun et al, , 2019. Central to GCN analysis is the 'guilt-by-association' principle whereby genes that share common functions or related processes are often co-ordinately regulated across a wide range of conditions (e.g., multiple tissues, developmental stages, stress, hormones, etc.).…”
Section: Identifying New Candidates For the Remaining Steps Of Ta Biomentioning
confidence: 99%
“…It was reported that an organ-specific expression pattern is established by AtPRB1, which responds to ethylene and methyl jasmonate in Arabidopsis [48]. Ethylene response factor (ERF) transcription factor, VaERF092, from Amur grape binds the promoter GCC-box of VaWRKY33, leading to enhanced cold stress tolerance in Arabidopsis [49]. Together, these target genes of all hub lncRNAs were related to a number of functions, such as growth and development and response to abiotic and biotic stress, suggesting that lncRNAs play multiple functions in peanut.…”
Section: Discussionmentioning
confidence: 99%